White Gold: The True Cost of Cotton (Environmental Justice Foundation, 2005)
Verzio FF submission Cotton production in the Central Asian Republic of Uzbekistan represents one of the most exploitative enterprises in the world...despite these well known abuses Western corporations and particularly European companies, continue to trade with the regime, buying cotton in exchange for vast amounts of foreign capital.